Endothelial progenitor cells enhance blood–brain barrier permeability in subacute stroke. (9th January 2018) - Sargento-Freitas, João; Aday, Sezin; Nunes, César; Cordeiro, Miguel; Gouveia, Ana; Silva, Fernando; Machado, Cristina; Rodrigues, Bruno; Santo, Gustavo Cordeiro; Ferreira, Carlos; Amorim, André; Sousa, Susana; et al.
Abstract : Objective: To study the association among endothelial progenitor cells (EPCs), subacute blood–brain barrier (BBB) permeability, and clinical outcome after ischemic stroke, determining the micro RNAs of EPCs responsible for good clinical outcome. Methods: We included consecutive patients with nonlacunar acute ischemic strokes in the territory of a middle cerebral artery and ages between 18 and 80 years. Clinical outcome was defined as modified Rankin Scale score at 3 months. Neuroimaging was performed at day 0 and 7 by MRI, including assessment of BBB permeability by dynamic contrast enhancement. EPCs were isolated from peripheral venous blood, quantified, and submitted to in vitro functional tests, including migratory and angiogenic assays. Stroke hemodynamics were evaluated serially by ultrasound. Statistical significance was set at p < 0.05. Results: We included 45 patients; mean age was 70.0 ± 10.0 years. The in vitro functional properties of EPCs were associated with BBB permeability, particularly at day 7. The number of each EPC subset at both timepoints was not associated with BBB permeability. Permeability of BBB at day 7 was independently associated with improved clinical outcome (odds ratio 0.897; 95% confidence interval 0.816–0.986; p = 0.025). The EPCs (CD34+ cell subset) of patients with good clinical outcome showed 24 differentially expressed miRNAs, with a common effect on adherens junction pathway. Conclusions: The functional properties of EPCs are associated with enhanced subacute permeability of BBB and improved clinical outcome after acute ischemic stroke.